Design of tunnel robot for inspection of large-diameter sewerage tunnel - Law, Wei Chuan (2017)
The used water superhighway is designed for used water collection, treatment, reclamation and disposal for the next 100 years of Singapore. It consists of trunk sewer, link sewer network and deep tunnel sewerage system. Tunnel maintenance is important to ensure the tunnel is in good working order to prolong its operating life. In-pipe robot is one of the important concepts to achieve automated tunnel maintenance such as inspection, cleaning and repairing because it can eliminate the risks that human always encounter in the tunnel. In order to identify available technologies that can be adopted in the design of the tunnel maintenance system, a study aimed to review existing pipeline and tunnel robots as well as hoisting system is then carried out. The robots can be classified into nine types of robotic system, namely PIG, Wheels, Crawler, Cylindrical, Legs, Inchworm, Helical, Snake and VVPIG type. The study implies that the research on pipeline and tunnel robot has been focusing on the maintenance of small diameter pipelines and it is seen that most of them just aim for short distance inspection. The scope of this works is to design a tunnel robot with a complete inspection system for large diameter tunnel inspections and a hoisting system for robot deployment. The robot must be water-proof, able to avoid sediment in the tunnel and has enough traction force for locomotion in the slippery condition. In this report, a preliminary design of the platform based on two types of locomotion, i.e. tracked and wheeled robot is carried out. Both track-based and wheel-based robots are simulated in CAD model to evaluate the functionality and feasibility of the design concept. The conceptual and detailed design of the robot chassis and the actuation mechanism to control the angle of the wheel frames will be covered in the subsequent chapters. The wheel frames are able to unfold to a certain angle to avoid the possible presence of soft debris along the bottom of the sewers. The robot will be designed as modules and assembled at the bottom of the access shaft. An overview of the configuration of the hoisting system for the deployment of the robotic platform has been presented. The whole system is composed of a number of subsystems, namely robotic platform, hoisting and winch system, ground control station and auxiliary system.